2016
DOI: 10.7906/indecs.14.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Commitment to Business Ethics to Nonfinancial Business Performance

Abstract: The article investigates the relationship between commitment to business ethics and nonfinancial business performance. Data of commitment to business ethics and nonfinancial business performance were collected from 100 participants through a questionnaire survey. The survey was conducted in 2015 in Croatian large and medium sized companies. The questionnaire for assessing commitment to business ethics contained nine different dimensions while the nonfinancial business performance contained three dimensions: cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…An extensive number of studies have shown the influence of management commitment on employees' performance and outcomes in various aspects (e.g. safety, service quality, employee behavior, financial performance and non-financial performance) Michael et al, 2005;Kim et al, 2009;Babakus et al, 2003;Verschoor, 1998;Vig and Dumicic, 2016). How employees perceive organizational support plays an important role in individual engagement with CSR activities (Lamm et al, 2015).…”
Section: Factors Affecting Unethical Behaviormentioning
confidence: 99%
“…An extensive number of studies have shown the influence of management commitment on employees' performance and outcomes in various aspects (e.g. safety, service quality, employee behavior, financial performance and non-financial performance) Michael et al, 2005;Kim et al, 2009;Babakus et al, 2003;Verschoor, 1998;Vig and Dumicic, 2016). How employees perceive organizational support plays an important role in individual engagement with CSR activities (Lamm et al, 2015).…”
Section: Factors Affecting Unethical Behaviormentioning
confidence: 99%
“…A commitment to business ethics can have an impact on nonfinancial performance for an organization. Vig and Dumičić (2016) evaluated whether a commitment to business ethics had a positive influence on nonfinancial performance including HRM, client satisfaction, innovation and efficiencies in business processes. When measuring dimensions of ethical behavior against the three nonfinancial measures, motivation, rewarding policy for ethical behavior, and responding to unethical behavior provided the most increase in nonfinancial performance.…”
Section: Financial Issues and Public Demandsmentioning
confidence: 99%
“…As the impression that company's leave in the public eye has gotten ever more important and the demands of the stakeholders have risen, many companies have realized that they have to implement ethical business standards, most often defined by programs of business ethics, which consist of: (1) values and mission, (2) codes of ethics, (3) ethics officers, (4) ethics helpline, (5) ethics training programs, (6) communicating ethical values, (7) rewarding policy for ethical behavior, and (8) ethics audit (Vig and Dumičić, 2016). The value and mission on which a company bases its business activity make up an ideological core, or rather, identity, the so called, character of a company (Collins and Porras, 2002).…”
Section: Business Ethics As a Premise For Good Corporate Reputationmentioning
confidence: 99%